The Influence of Job Training and Work Discipline on Employee Performance at PT Maju Lancar Sejahtera in the City of Depok, West Java, Indonesia - Suwanto (Sinergi International Journal of Management and Business, 2023)
The objective of this research is to determine the influence of job training and work discipline on employee performance at PT Maju Lancar Sejahtera. The method used is quantitative. The sampling technique employed is saturated sampling with 75 respondents as the sample. Data analysis involves validity testing, reliability testing, classic assumption testing, regression analysis, correlation coefficient analysis, determinant coefficient analysis, and hypothesis testing. The research results indicate that training significantly influences employee performance with a correlation coefficient of 0.837, indicating a moderate relationship. The determinant value is 0.701 or 70.1%, while the remaining 29.9% is influenced by other factors. Hypothesis testing reveals that the calculated t-value > t-table (13.067 > 1.993), so H0 is rejected, and H1 is accepted. This means there is a significant partial influence of job training on employee performance. Similarly, work discipline significantly influences employee performance, with a correlation coefficient of 0.901, indicating a strong relationship. The determinant value is 0.812 or 81.2%, while the remaining 18.8% is influenced by other factors. Hypothesis testing shows that the calculated t-value > t-table (17.755 > 1.993), thus rejecting H0 and accepting H1. This implies a significant partial influence of work discipline on employee performance. Furthermore, both job training and work discipline significantly influence employee performance, with a correlation coefficient of 0.909 indicating a strong relationship. The determinant value is 0.827 or 82.7%, while the remaining 17.3% is influenced by other factors such as compensation, work environment, and work discipline. Hypothesis testing reveals that the calculated F-value > F-table (171.837 > 1.993), rejecting H0 and accepting H1. Therefore, there is a significant simultaneous influence of job training and work discipline on employee performance.